Fertility Preservation in Cancer Patients During the Coronavirus (COVID-19) Pandemic - Dellino, Miriam; Minoia, Carla; Paradiso, Angelo Virgilio; De Palo, Raffaella; Silvestris, Erica (Frontiers in Oncology, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also identified as Corona virus disease 19 (COVID-19), has recently produced a dramatic and widespread sanitary emergency. However, despite the necessity to assist a substantial number of affected patients, it is also essential to, at the same time, guarantee the usual clinical care, particularly to cancer patients, including fertility preservation (FP) strategies before the beginning of the anti-cancer treatments. The FP techniques for adult female patients include oocyte and embryo cryopreservation, which require both adequate ovarian reserve (OR) and controlled ovarian stimulation (COS) to promote multiple follicular growth. However, ovarian tissue cryopreservation is an additional FP practice suitable when an anti-cancer treatment is urgently required, whereas, for male patients, sperm cryopreservation is a simple and well-adopted procedure. Here, we focus on the current conditions in terms of agreements and rules of FP procedures during this COVID-19 pandemic to achieve and provide useful recommendations for the adoption of these techniques in patients with cancer.